PEMANFAATAN DATA PENGINDERAAN JAUH UNTUK MENDUKUNG PERENCANAAN OPERASI KEAMANAN LAUT DI LAUT ARAFURU - Winarso, Gathot; Kurniawan, Eko (Institut Teknologi Sepuluh Nopember, 2014)
Large sea area has been patrolled continuly by Indonesia Navy need a lot of fleets to cover all Indonesian seawaters and also spend a huge of budget. Consequently, it is important to have smart strategic to optimise the fleet and to make efficient the logistic budget. The objective of this research is to apply remote sensing analysis to get sensitive timing operation on violation and security disturbance related to fishing activity. According to assumption that security threat might occur in the area where fishing activity is high that will be concentrated in the high productivity area. The chlorophyll-a concentration estimated from satellite data MODIS level-2 were received from NASA United State of America. Daily data from 2008-2013 was calculated into monthly average to get monthly variation of chlorophyll-a concentration within a year during 5 years. The analysis was done in general area and smaller unit area to understand the different variation at smaller area. The variation of chlorophyll-a in smaller unit area will differ the plan timing in patrol activity specific for those area. The data analysis resulted that phytoplankton bloom indicated occurred to May- September every year. The month of phytoplankton bloom can be suggested become a more intense patrol activity. In general, there are no different result from smaller unit area, but only small shifting of timing of bloom and changing of each different unit area.